Knowledge communication model of social network with user cooperation and leadership encouragement - Qiuyang GU; Chunhua JU; Gongxing WU (Dianxin kexue)
In recent years,social networks have become a common medium for users to share knowledge.The knowledge communication in the social network environment was modeled and researched,with a hope to provide reference for relevant departments to effectively implement supervision and improve users’ knowledge exchange efficiency.Based on the classic SIS and SIR models,factors such as user cooperation and leadership encouragement for optimization were integrated,and the replication of dynamic equations was combined to construct and analyze two social network user knowledge communication models (SISL /SIRL).Finally,the data and model examples were given.The results show that the speed of knowledge communication is faster in social networks with leaders.In the process of social network knowledge communication,the number of vulnerable users decreases while that of the immune users increases,and the number of infected users fluctuates within a small range.Compared with the classic model and the real social network,the knowledge communication model constructed has a stronger fit.